Comparative Analysis of Cargo Flows on Branches VB and VC of the Pan-European Corridor V - Poletan Jugović, Tanja; Jolić, Natalija; Kavran, Zvonko (Promet - Traffic&Transportation, 2012)
Pan-European Corridor V that passes through the territory of the Republic of Croatia, i.e. Branches VB (Rijeka-Zagreb-Budapest) i VC (Budapest-Osijek-Sarajevo-Ploče) are of extreme importance for the traffic and economic system of the Republic of Croatia and the wider European area. Taking this into consideration, this study has analysed the relevant indicators of the traffic growth, structure and dynamics of the cargo flows on the Branches VB and VC of the Pan-European Corridor V. The cargo flows, as important elements of the traffic demand have been analysed regarding the presence of competition of alternative North-Adriatic and North-European traffic routes as important element of competitive environment in fighting to attract valuable transit market of Central Europe. Based on a detailed analysis of concrete statistical data, significant conclusions are derived about: quantity, dynamics and structure of the cargo flows, current traffic demand, competitiveness of corridors on Central European transit market, expected traffic demand, and conclusions about factors and circumstances that would positively, i.e. negatively affect the growth of cargo flows, and thus also the valorisation of the analysed Branches VB and VC of the Pan-European Corridor V within the European environment.KEY WORDS: Pan-European Corridor V, branches VB and VC, cargo flows, intensity, structure, dynamics, traffic demand